SISTEM PAKAR DIAGNOSA PENYAKIT UDANG VANAME PADA DINAS KELAUTAN DAN PERIKANAN PROVINSI BANTEN - Ma'sum Ma'sum; Wahidin Wahidin (Journal of Innovation And Future Technology (IFTECH), 2020)
Department of Marine and Fishery in Banten Province is one of the government agencies that are also an integral part of national development which attempted to walk in a harmonious, effective, efficient, and sustainable by empowering all potential areas owned and managed by the local government to be critical to the success of the capital development to improve the welfare of the community in Banten Province. In this regard, Marine and Fisheries office in Banten Province have a responsibility to prevent the spread of diseases especially white shrimp disease. incidence of the disease in a farming area is one of hindering the development of shrimp farming. So, the writer wants to give another alternative that can overcome existing problem by building a “VANAME SHRIMP DISEASE DIAGNOSIS EXPERT SYSTEM ON MARINE AND FISHERIES DEPARTMENT IN BANTEN PROVINCE”. This expert system designed to help the farmers in diagnosing disease early white shrimp and get information about the types of disease. In this expert system design, the user input symptoms suffered, then the output generated by the computer in the form of disease experienced by users and how to control the disease at white shrimp.